Production-based teaching factory learning model: Enhancing soft skills and simulating the industrial environment - Setiadi, Anwar; Rochayati, Umi; Hartopo, Ibnu; Handito, Tri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
According to the Central Statistics Agency, the high unemployment rate among vocational school graduates is caused by the mismatch between their technical competencies and professional character with industry needs. Vocational schools aim to prepare graduates with excellent skills and character for the business and industrial world. This study aims to create a teaching factory learning model at SMK 1 Perguruan Cikini using the Research and development method with the 4D model (define, design, develop, and disseminate). The study resulted in a 4P+QD teaching factory model, which consisted of divisions such as project sales, PPIC, production, purchasing, quality control, delivery, and after-sales. The model was validated by two expert lecturers, resulting in an average score of 3.54 (“Very Valid”). Evaluations by two productive subject teachers yielded a score of 3.71 (“Very Valid”), while assessments from the teaching factory coordinator and industry practitioners resulted in a score of 3.33 (“Valid”). The model was also tested on students, who evaluated the development of character traits such as honesty, discipline, responsibility, cooperation, adaptability, and creativity, with an average score of 3.47 (“Valid”). This learning model can serve as a reference for vocational high schools (SMK) seeking to implement production unit-based or teaching factory learning processes.